(untitled) (Journal of Health Sciences, 2013)
Introduction: Preterm delivery is the delivery before 37 weeks of gestation are completed. The incidence of preterm birth ranges from 5 to 15%. Aims of the study were to determine the average body weight, Apgar score after one and five minutes, and the frequency of the most common complications in preterminfants.Methods: The study involved a total of 631 newborns, of whom 331 were born prematurely Aims of this study were to (24th-37th gestational weeks-experimental group), while 300 infants were born in time (37-42 weeks of gestation-control group).Results: Average body weight of prematurely born infants was 2382 grams, while the average Apgar score in this group after the fi rst minute was 7.32 and 7.79 after the fifth minute. The incidence of respiratory distress syndrome was 50%, intracranial hemorrhage, 28.1% and 4.8% of sepsis. Respiratory distresssyndrome was more common in infants born before 32 weeks of gestation. Mortality of premature infants is present in 9.1% and is higher than that of infants born at term.Conclusions: Birth body weight and Apgar scores was lower in preterm infants. Respiratory distress syndrome is the most common fetal complication of prematurity. Intracranial hemorrhage is the second most common complication of prematurity. Mortality of premature infants is higher than the mortality of infants born at term birth.